1985
DOI: 10.2134/agronj1985.00021962007700060011x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Compaction and Moisture Stress Preconditioning in Kentucky Bluegrass. I. Soil Aeration, Water Use, and Root Responses1

Abstract: Soil compaction and moisture stress are major problems on recreational turfgrass sites. In the greenhouse, we investigated root responses to soil compaction and moisture stress preconditioning, and their effects on water use of Kentucky bluegrass (Poa pratensis L. 'Ram 1'). The compaction treatments included: (i) NC = no compaction, (ii) LT = long-term compaction (equivalent to 720 J energy) over a 99-day period, and (iii) ST = short-term compaction for 9 days. Irrigation regimes were initiated at the same tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
3
26
1
2
Order By: Relevance
“…Previous reports (AGNEW and CARROW 1985;BAR-YOSEF and LAMBERT 1981) have indicated that the influence of soil compaction on water uptake is not consistent. AGNEW and CARROW (1985) found that compaction decreased the total water use but increased the water use efficiency of roots for Kentucky bluegrass grown on a silt loam.…”
Section: Water Use By Plantsmentioning
confidence: 86%
“…Previous reports (AGNEW and CARROW 1985;BAR-YOSEF and LAMBERT 1981) have indicated that the influence of soil compaction on water uptake is not consistent. AGNEW and CARROW (1985) found that compaction decreased the total water use but increased the water use efficiency of roots for Kentucky bluegrass grown on a silt loam.…”
Section: Water Use By Plantsmentioning
confidence: 86%
“…The reports on the effects of soil compaction on water-uptake by the plants are inconsistent. The water uptake by Kentucky bluegrass (Agnew and Carrow, 1985), pigeon pea (Kirkegaard et al, 1992), and maize (Amato and Ritchie, 2002) was decreased by soil compaction. On the other hand, Lipiec et al (1988) indicated that water uptake by maize was enhanced by higher soil bulk density.…”
mentioning
confidence: 96%
“…Agnew and Carrow, 1985;Engelaar et al, 2000;Trautner and Arvidsson, 2003), few investigators have studied the root growth responses to different levels of combined soil physical stresses. Among them, Eavis (1972) used the pea radicle grown in a sandy loam soil under different levels of soil water potential and soil bulk density, and measured the length and diameter of the radicle as the criteria of the combined stresses under different levels of soil water, air and impedance status.…”
mentioning
confidence: 99%